The One21 Technique: An Individualized Treatment for Glabellar Lines Based on Clinical and Anatomical Landmarks [Corrigendum] - de Sanctis Pecora C; Pinheiro MVB; Ventura Ferreira K; Jacobino de Barros Nunes G; Miot HA (Dove Medical Press, 2021)
de Sanctis Pecora C, Pinheiro MVB, Ventura Ferreira K, Jacobino de Barros Nunes G, Miot HA. Clin Cosmet Investig Dermatol. 2021;14:97–105. The authors have advised due to an error at the time of figure assembly, Figure 5 on page 103 is incorrect. The correct Figure 5 is shown below. The authors apologize for this error and advise it does not affect the results of the paper. Read the original article